Dominee Nicolaas Beets: "De familie Kegge" (1851) in het perspectief van de afschaffing van de slavernij - Rutgers, Wim (Department of Dutch and South African Studies, Faculty of English, 2013)
Edward W. Said, Culture and Imperialism (1993) offers opportunities for rereading and re-interpretation of canonical historical literary works by way of focussing on the relation between culture and empire. Nicolaas Beets, “De familie Kegge,” seems to be a good example for this “contrapuntal reading.” The short novel protests in a mild way against slavery and behaviour of slave owners and plantation owners in the Caribbean. In later work Beets proves to have become a fierce anti-slavery advocate, an aspect of his work that until now is hardly ever discussed and has been neglected in traditional criticism.
Keywords: Dutch literature in the 19th century; Edward W. Said; contrapuntal reading; Caribbean sugarplantations; slavery and anti-slavery movement in the Netherlands; imperialism; interpretation problems; canon